Unholy Wars : Afghanistan, Americe and International Terroorism - Cooley, John K. (London Pluto Press, 2000)
To oppose the Soviet invasion of Afghanistan in 1979, the US formed an anti-communist alliance with militant Islamic forces in Central Asia. This book provides an account of this alliance and how the CIA planned and ran a holy war in Afghanistan.
Include Maps and Index
Keywords: Terrorism -- United States -- Afghanistan -- Diplomatic relations -- Espionage, American